Sepsis: Current Concepts - Nuruzzaman, Md (Bangladesh Journal of Medicine, 2023)
Sepsis is a life-threatening syndrome caused by an exaggerated host immune response to infection. Despite advances in diagnosis and treatment, sepsis remains a major global health concern, with significant morbidity and mortality rates. Current concepts in sepsis management emphasize the need for early recognition and treatment of the condition, with a focus on the optimization of fluid resuscitation, antibiotic therapy, and supportive care. Recent studies have shown that a multifaceted approach to sepsis management, involving a combination of pharmacological and non-pharmacological interventions, may improve outcomes. This approach includes the use of biomarkers for early diagnosis, goal-directed therapy to optimize resuscitation, and the implementation of protocols for timely initiation of appropriate antimicrobial therapy. Furthermore, recent studies have highlighted the importance of individualized patient care in sepsis, with a focus on tailoring treatment to the specific needs of the patient. There is also growing interest in the use of novel therapies for sepsis, such as immunomodulatory agents, extracorporeal therapies, and stem cell therapies. These therapies have shown promising results in preclinical studies, and may provide new avenues for the treatment of sepsis in the future. Overall, the current concept of sepsis management emphasizes early recognition and intervention, individualized patient care, and a multifaceted approach to treatment. Further research is needed to identify optimal approaches to sepsis management and to develop novel therapies for this complex condition. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 195